2007
DOI: 10.1111/j.1745-7254.2007.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain induces cardiac remodeling in rats independent of blood pressure

Abstract: Aim: To investigate the ouabain's effects on cardiac remodeling in rats. Methods: Male Sprague‐Dawley rats were treated with ouabain. Systolic blood pressure (SBP) was recorded weekly. After 4 and 6 weeks, echocardiography were performed, hemodynamic parameters were measured by invasive cardiac catheterization, changes in cardiac ultrastructure were analyzed using transmission electron microscopy, the collagen fraction of the left ventricle was assessed with Picrosirius red stain, and RT‐PCR was applied to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
11
0
3
Order By: Relevance
“…In addition, several reports, including the present study, have also demonstrated that there is a correlation between EO and endothelial dysfunction (12,23,24). In the present study, certain significant pathological ultrastructural changes were also identified in rat apical mid-myocardium, in accordance with the findings of a previous study (25). We successfully constructed an experimental animal model of hypertension using intraperitoneal EO injection.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, several reports, including the present study, have also demonstrated that there is a correlation between EO and endothelial dysfunction (12,23,24). In the present study, certain significant pathological ultrastructural changes were also identified in rat apical mid-myocardium, in accordance with the findings of a previous study (25). We successfully constructed an experimental animal model of hypertension using intraperitoneal EO injection.…”
Section: Discussionsupporting
confidence: 93%
“…Gene replacement studies (in which the ouabain-resistant mouse Na/K-ATPase α1 subunit was replaced with ouabain-sensitive humanized α1 subunit) have unequivocally demonstrated an important role of endogenous CTS in the regulation of renal sodium excretion and BP in rodents [54,55]. CTS also cause significant oxidative stress and cardiovascular remodeling independent of their effect on BP [56,57,58,59]. …”
Section: The Concept Of “Natriuretic Hormone” and Renal Sodium Hanmentioning
confidence: 99%
“…The data suggest that the observed CTS-induced natriuretic effect might be a result of the combined effects of ouabain and MBG [60]. Furthermore, CTS not only induced hypertension in rats but also caused significant cardiovascular remodeling and natriuresis independent of their effect on BP [49, 51, 70, 80, 81]. …”
Section: Cts and Sodium Homeostasismentioning
confidence: 99%